Lipid-polymer hybrid nanoparticle with cell-distinct drug release for treatment of stemness-derived resistant tumor - Shiyang Shen; Teng Li; Jinyi Fan; Quanlin Shao; He Dong; Xiao Xu; Ran Mo (Elsevier, 2023)
Drug resistance presents one of the major causes for the failure of cancer chemotherapy. Cancer stem-like cells (CSCs), a population of self-renewal cells with high tumorigenicity and innate chemoresistance, can survive conventional chemotherapy and generate increased resistance. Here, we develop a lipid-polymer hybrid nanoparticle for co-delivery and cell-distinct release of the differentiation-inducing agent, all-trans retinoic acid and the chemotherapeutic drug, doxorubicin to overcome the CSC-associated chemoresistance. The hybrid nanoparticles achieve differential release of the combined drugs in the CSCs and bulk tumor cells by responding to their specific intracellular signal variation. In the hypoxic CSCs, ATRA is released to induce differentiation of the CSCs, and in the differentiating CSCs with decreased chemoresistance, DOX is released upon elevation of reactive oxygen species to cause subsequent cell death. In the bulk tumor cells, the drugs are released synchronously upon the hypoxic and oxidative conditions to exert potent anticancer effect. This cell-distinct drug release enhances the synergistic therapeutic efficacy of ATRA and DOX with different anticancer mechanism. We show that treatment with the hybrid nanoparticle efficiently inhibit the tumor growth and metastasis of the CSC-enriched triple negative breast cancer in the mouse models.